A comparison between web enhancer learners and blended learners in flipped classroom: A quasi-experimental approach - Nasirun, Noraini (International Academic Research Journal, 2015)
Blended learning integrates technologies in classroom activities.This development is considered as a strategic approach for digital native generation The exposure of the technology to this generation since the early age requires a new approach to leverage their capabilities in learning.Currently, in Malaysia, the education landscape promotes various approaches related with blended learning including flipped classroom.This situation indirectly confirms that there is no traditional learning in the universities, especially in the public universities. Unfortunately, most of the studies about online learning made comparison between online learning and traditional learning.Little of these studies focus about the differences of online interaction exposure has impact on students.Hence this aim of is study is to investigate the significant differences of online exposures among students in blended learning environment.Data were collected using non randomized quasi experimental approach among business students in a public university in Malaysia. Data analysis shows a mix result where there were significant differences between groups for satisfaction, effectiveness, efficiency and student interactions.However, there were no significant difference for student engagement and final result for both of the studied groups. Conclusion and recommendation also discussed in this article.